Institutions, Resilience, and Dynamic Capabilities of Entrepreneurial Ecosystems in Emerging Economies - Inder, Shivani, 1984-; Singh, Amandeep, 1982-; Sharma, Sandhir, 1974- (Hershey PA: IGI Global, 2022)
"This book will strengthen the research into the role of entrepreneurship in economic growth in emerging economies and how entrepreneurship is shaping the future of emerging markets"--
Includes bibliographical references and index.
Keywords: Entrepreneurship -- Developing countries; Economic development -- Developing countries